INVESTIGATING THE EFFECTIVENESS OF NURSE NAVIGATORS IN IMPROVING CARE COORDINATION AND REDUCING HOSPITAL READMISSIONS - Saleh Mhawesh Jkhedem Alenaze, Thamer Awad Hazzaa Alshammari, Wael Abdullah Mohammed Aljurbua, Fayez Sayer Awdah Alshammari, Murdhi Ghathith Olyan Alshammari, Ayed Farhan Thani Alanizi, Faisal Mazyad Khalif Alkhaldi, (Chelonian Research Foundation, 2022)
Hospital readmissions are a significant challenge for healthcare systems, with implications for patient outcomes and costs. Nurse navigator programs have emerged as a promising approach to improving care coordination and reducing readmissions, but evidence on their effectiveness in general patient populations is limited. Objective: To evaluate the impact of a hospital-wide nurse navigator program on 30-day readmissions and patient-reported care coordination in a diverse patient population. Design: Mixed-methods study with a quasi-experimental design and qualitative provider interviews. Setting: Large, urban academic medical center. Participants: 1,258 adult patients admitted to medical, surgical, or cardiac units and 25 healthcare providers. Intervention: Nurse navigator program providing individualized care coordination and support from admission to 30 days post-discharge. Main Measures: Primary outcome was 30-day all-cause readmissions. Secondary outcomes included 30-day emergency department visits, patient-reported care coordination (Care Transitions Measure), and discharge preparedness (B-PREPARED scale). Key Results: The 30-day readmission rate was 18.2%. In adjusted analyses, the intervention group had significantly lower odds of readmission compared to the comparison group (OR 0.72, 95% CI 0.55-0.94). Intervention patients also had lower rates of 30-day emergency department visits and higher patient-reported care coordination and discharge preparedness. Qualitative themes highlighted the importance of navigators as bridge-builders, challenges of role clarity and integration, and the need for dedicated resources and training. Conclusions: A nurse navigator program reduced readmissions and improved care coordination in a diverse patient population. The results support the effectiveness of nurse navigators as a strategy for improving transitional care and patient outcomes.